Pengaruh Kompetensi dan Disiplin Kerja Terhadap Efektivitas Kerja dengan Motivasi Kerja Sebagai Variabel Mediasi pada Perangkat Nagari Sekecamatan Lubuk Sikaping Pasaman - Rusydan, Rusydan; Putri, Eka Risma (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to determine the influence of competency and work discipline on work effectiveness with work motivation as a mediating variable in the Nagari Device of Lubuk Sikaping Subdistrict, Pasaman. The sample consists of 85 Nagari Devices from Lubuk Sikaping Subdistrict, Pasaman. The method used is survey analysis with data analysis techniques of outer model testing, inner model testing, and hypothesis testing. The type of research used is quantitative. The sample consisted of 85 village officials in Lubuk Sikaping District, Pasaman. The results showed that competence had a significant positive effect on work effectiveness. Work discipline had a significant positive effect on work effectiveness. Work motivation had a significant positive effect on work effectiveness. Competence had a significant positive effect on work motivation. Work discipline had a significant positive effect on work motivation. Work motivation mediated the effect of competence on work effectiveness. Work motivation mediated the effect of work discipline on work effectiveness.